ILMU PENGETAHUAN DALAM PANDANGAN AL-QUR’AN DAN IMPLEMETASINYA DALAM PEMBELAJARAN SAINS - Tursinawati .; Israwati .; Putry Julia (Jurnal Pesona Dasar, 2020)
Science is a way for humans as a guide in making decisions in life. AL-Qur'an places knowledge as an obligation to learn. Therefore, it is important to teach children to study knowledge from the Al-Quran. The purpose of this research is to examine the verses of the Al-Qur'an about science in science learning. This study used a literature review design with the steps of collecting library data, reading and taking notes, and comparing the literature to be processed and producing conclusions. The data used are secondary data from textbooks, journals, scientific articles, literature reviews that contain the concepts studied. Based on the results of a literature review, it can be concluded that science has aspects such as scientific problems; scientific attitude; scientific method; scientific research; conclusion; and the influence on technology and society. In the view of the Al-Qur'an, studying knowledge must be based on chanting and remembering the name of Allah. Allah made this universe as a medium for human study through a series of activities to read, write, study, research, investigate, observe, and appreciate the greatness of God Almighty in creation. Sight, hearing, and conscience are valuable learning tools or instruments so that they can increase faith and piety in God Almighty. The implementation of science learning can be carried out by internalizing the values of tauhid through studies of the Qur'an related to science. Internalization of monotheistic values or belief in religion in learning can be carried out by 1) curriculum integration, 2) learning integration, and 3) science integration (Islamization of science). Besides that, it can also be applied by exemplary, actual problems in society, planting educational values contextually, and strengthening moral values.